PEMBERIAN BEBERAPA DOSIS PUPUK NPK DAN KONSENTRASI AIR CUCIAN BERAS TERHADAP HASIL TANAMAN TOMAT (Lycopersicum esculentum Mill.) - Sefrianti, Raja Hikmah Nur; Nurbaiti, Nurbaiti Nurbaiti; Adiwirman, Adiwirman Adiwirman (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2019)
This study aims to determine the interaction effect of giving NPK fertilizer dosage with the concentration of washed rice water, the influence of a single factor giving a dose of NPK fertilizer and the concentration of washed rice water to the yield of tomato plants (Lycopersicum Esculentum Mill.).This study used a Completely Randomized Factorial Design (CRD) consisting of two factors and three replications. The first factor in administering NPK (P) doses consisted of four levels, P0: Without NPK fertilizer, P1: NPK 125 kg.ha-1, P2: NPK 250 kg.ha-1 and P3: NPK 375 kg.ha-1. The second factor is the concentration of washed rice water (L) consisting of four levels, L0: 0%, L1: 50%, L2: 75% and L3: 100%. The data were analyzed statistically using a variety of linear model examination, the data had significant effect followed by an Honest Significant Difference test (BNJ) at the level of 5%. The parameters observed the age parameters of flower appearance, age of first harvest, number of fruits per plant, weight per plant, weight per fruit and fruit yield per hectare.The results showed that the interaction of NPK fertilizer and washed rice water concentration significantly affected the parameters of fruit weight per plant, weight per fruit and fruit yield per hectare, but it did not significantly influence the age parameters of flower appearance, age of first harvest and number of fruits per plant. Provision of 375 kg.ha-1 of NPK fertilizer and the concentration of 75% washed rice water accelerated the age of flower appearance and age of the first harvest, the highest number of fruits, fruit weight per plant, weight per fruit and highest yield per hectare in tomato plants.Keywords :Plant tomatoes, NPK, Washed rice water